(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article substantiates the importance of using lexical expressive means in the speech of a German language teacher. The authors identify several groups of lexical means of creating expressiveness within the framework of interaction between teacher and student. A number of lexical means of expressiveness are clichéd in nature, which reduces their emotive potential. Metaphors, epithets and irony have a high degree of expressiveness in pedagogical discourse.